Keputusan Pembelian melalui Marketplace Shopee ditinjau dari Celebrity Endorser, Online Customer Review dan Rating - Dyah Ayu Fajar Arini; Sri Hartono; Istiqomah Istiqomah (LPPM Institut Nasional Laa Roiba Bogor, 2022)
This study aims to determine whether there is a significant influence between the celebrity endorser, online customer review, and rating variables on purchasing decisions through the shopee marketplace for high school students in Surakarta. The method used is a quantitative method. The population in this study were high school students in Surakarta and the sample used was 100 respondents. The sampling technique in this study is non-probability sampling with a purposive sampling approach. The types of data used in this study are primary data and secondary data. The data collection technique uses observation, documentation, questionnaires, and literature studies. The data analysis technique in this study is the classical assumption test, multiple linear regression and the coefficient of determination. The results of this study stated that the celebrity endorser variable had a positive and significant effect on purchasing decisions because the results of SPSS calculations obtained t count > t table (5.965> 1.985) and sig. of 0.000 is less than 0.05. The online customer review variable has a positive and significant effect on purchasing decisions because the SPSS calculation results obtained t count > t table (3.481>1.978) and sig. of 0.001 is smaller than 0.05. While the rating variable is also stated to have a positive and significant effect on purchasing decisions because the results of SPSS calculations obtained t count > t table (3.453>1.978) and sig. of 0.001 is smaller than 0.05. Keywords: Purchase Decision, Celebrity Endorser, Online Customer Review, Rating.